Comparative immunologic characterization of autoimmune giant cell myocarditis with ipilimumab. (2nd December 2017) - Reuben, Alexandre; Petaccia de Macedo, Mariana; McQuade, Jennifer; Joon, Aron; Ren, Zhiyong; Calderone, Tiffany; Conner, Brandy; Wani, Khalida; Cooper, Zachary A.; Tawbi, Hussein; Tetzlaff, Michael T.; Padera, Robert F.; et al.
ABSTRACT: Autoimmune myocarditis is a rare but often fatal toxicity of checkpoint inhibitor immunotherapy. To improve the understanding of this complication, we performed immune profiling on post-mortem tissue from a patient with metastatic melanoma who had steroid-responsive hepatitis, steroid-refractory myocarditis, and shrinking lung metastases after ipilimumab treatment. Histological analysis of heart tissue demonstrated findings consistent with giant cell myocarditis (GCM). The immune infiltrate in the heart was largely comprised of CD4+ T cells, whereas the liver had very few T cells, and CD8+ T cells were predominant in the responding lung metastases. TCR sequencing identified high T cell clonality in the lung metastases. The TCR repertoire showed low clonality in the heart and minimal overlap with the liver (1.2%), but some overlap with lung metastases (9.9%). Transcriptional profiling identified several potential mediators of increased inflammation in the heart. These findings provide new insights into the pathogenesis of autoimmune myocarditis with ipilimumab.